Global trends in fall-induced hip fractures among perimenopausal women 1990 to 2021: results from the global burden of disease study 2021 - Wang, Zhen; Chen, Zijian; Zhang, Chaoyi; Liu, Wenzheng; Liu, Jixi; Lin, Wei; Wang, Guanglin (Frontiers in Public Health, 2025)
BackgroundFall-induced hip fractures in perimenopausal women (FHFPW) are major clinical and public health concern, contributing significantly to global morbidity. This study examines the global impact of FHFPW, focusing on the prevalence, incidence, and years lived with disability (YLDs) across different age groups, regions, and levels of Socio-demographic index (SDI) from 1990 to 2021. The aim is to provide epidemiological data that can inform health policies, and enhance strategies for the prevention and treatment of hip fractures in perimenopausal women.MethodsWe extracted registered data on incidence cases, prevalence cases, and YLD cases, along with the corresponding rates and their 95% uncertainty intervals (UIs), from the Global Burden of Disease (GBD) 2021 database. All rates in this study were expressed per 100,000 population. The estimated annual percentage change (EAPC) was used to assess changes in the burden of FHFPW and Spearman’s correlation tests were used to examine the relationship between SDI and the burden of FHFPW. The average annual percentage change (AAPC) was further calculated to evaluate temporal trends.ResultsThe disease burden of FHFPW was substantially higher in the 50-54-year age group than in the 45-49-year group. In 2021, there were 300,104 cases among women aged 50–54 years, compared with 164,196 cases in the 45-49-year group. From 1990 to 2021, although the absolute numbers of prevalent cases, incident cases, and YLDs increased, the corresponding incidence, prevalence, and YLDs rates declined. The burden was greater in high-SDI regions, particularly in Oceania, where the prevalence in the 50-54-year group demonstrated the most striking increase (+295.7%). Joinpoint analysis further indicated that, overall, prevalence and YLDs rates showed a downward trend, whereas incidence in the 50-54-year group within high-SDI regions exhibited the most pronounced rise (AAPC = 0.8%; p < 0.001).ConclusionThe global burden of disease for FHFPW remains high and tends to increase further; age is an important influencing factor. The burden of disease shows significant regional variations, with a higher burden of disease in regions with high SDI.